Aedes mosquito surveillance and the use of a larvicide for vector control in a rural area of the Lao People’s Democratic Republic - Pheophet Lamaningao; Seiji Kanda; Takaki Shimono; Somchit Inthavongsack; Thonelakhanh Xaypangna; Toshimasa Nishiyama (Tropical Medicine and Health, 2020)
Abstract Background Refillable water containers are commonly used in rural areas of Lao PDR, and they act as Aedes mosquito breeding sites. Aedes aegypti and Ae. albopictus mosquitos are transmission vectors for the dengue virus, which causes dengue fever. Methods Two isolated rural villages in the central part of Lao PDR were selected as study sites. In the intervention village, domestic water containers were continuously treated with a long-lasting matrix release formulation, containing pyriproxyfen, named SumiLarv®2MR. In the control village, entomological activity was monitored, but no intervention was performed. Baseline data were collected in both villages during the late rainy season (October 2017) then distributed SumiLarv®2MR disks in intervention village. This data was compared with data collected during the intervention periods in the dry season (February 2018), rainy season (July 2018 and 2019), and late rainy season (September 2018) in the region. Results Compared with the baseline data (20.24%), the percentage of water containers infested with Ae. aegypti larvae was significantly decreased in the treated village, especially in the rainy seasons in July 2018 (4.11%; P < 0.001) and July 2019 (2.46%; P < 0.001), while the percentage of water containers infested with Ae. albopictus larvae did not decrease significantly in prevalence. No reduction in the frequency of Aedes species was seen in the control village. The Ae. albopictus liked to breed in small habitats (the median water volume of its habitats was 5 L and 10 L in the control and treated village, respectively, while the equivalent values for Ae. aegypti were 30 L and 50 L, respectively). Conclusion The treatment of refillable water storage containers in a rural village with SumiLarv®2MR disks led to significant reductions in the Ae. aegypti population. However, the Ae. albopictus population did not decrease in either the control or treated village. This discrepancy was due to differences in habitat-seeking behaviors and preferred ...